Development of quality indicators of transfer and transition in adolescents and young adults with congenital heart disease - Corina Thomet; Philip Moons; Markus Schwerzmann; Fabienne Schwitz (BMC, 2023)
Abstract Background Quality indicators are crucial in evaluating and comparing the quality of healthcare services. In the case of congenital heart disease, transition programmes for adolescents have been recommended to ensure uninterrupted healthcare and lifelong care. It is necessary to establish quality indicators in order to facilitate the evaluation of programme quality and to allow comparison between different centres. The objective of this study is therefore to develop a set of quality indicators for the transition of adolescents with congenital heart disease. Methods The RAND/UCLA appropriateness method was employed in a four-step process to develop a set of quality indicators. First, a literature search was conducted on the dimensions of transitional care, based on which a preliminary set of quality indicators was developed. Second, experts were contacted, and an expert panel was established. Third, the panel members were asked to rate the appropriateness of the quality indicators in a two-round process. Finally, in the fourth step, we evaluated the data by measuring the median and Disagreement Index. Results The expert panel consisted of 16 members, congenital cardiologists, nurses, transition experts, patients and research experts. The preliminary set of quality indicators comprised 16 items, categorized in process and structure criteria. Based on the panel's feedback, the set was refined to 12 quality indicators, which were rated as relevant and feasible. Conclusions This study represents the first attempt to develop quality indicators for transitional care services for adolescents with congenital heart disease. The set of 12 quality indicators was developed based on existing evidence and expert opinion. Further testing is needed to assess the feasibility of these quality indicators in daily practice. If successfully implemented, these quality indicators could allow comparison and facilitate benchmarking of transitional care services for adolescents with congenital heart disease.